KETERAMPILAN PROSES SAINS SISWA SMA DALAM PEMBELAJARAN BIOLOGI - Maria Senisum (Jurnal Pendidikan dan Kebudayaan Missio, 2021)
Science process skills (SPS) are important for students to have because they are part of psychomotor competencies, which support students in the process of gaining knowledge. This research was conducted to provide an overview of the psychomotor abilities in the form of student SPS. The type of research used is descriptive qualitative research. There are two types of data collected in the study. The first data on SPS were collected by providing 20 multiple-choice questions that deal with the eight types of process skills. The second data is in the form of interviews relating to teachers' knowledge of SPS and learning approaches in teaching biology. The data sources came from 287 grade XI students with a specialization in mathematics and natural sciences and four teachers who teach biology from four different schools. The SPS data were analyzed descriptively. The results of the study show that the students' SPS is at a moderate level. Of the eight SPS tested on students, communication skills were the skills that got the highest score where 73.9% of students had these skills while concluding skills were the lowest skills where only 36.4% of students could have these skills. The results of the interview with the teacher show the fact that the lecture method is a method that is often applied by teachers when teaching biology. Practicum is rarely done by teachers for various reasons. Practicum in biology learning is important because with it students interact directly with objects of observation and can empower various competencies to answer problems in biology, including SPS.